ANALISIS SWOT DALAM PENGEMBANGAN KINERJA PADA KARYAWAN CV. ASANKA WIJAYA - Candra Yanuar; Recky Recky; Kartika Nuradina (Komunitas Manajemen Kompetitif, 2025)
Abstract This study analyzes employee performance in CV. Asanka Wijaya, a cosmetics company, uses a SWOT analysis. The goal is to identify strengths, weaknesses, opportunities, and threats that affect employee performance and formulate the right performance improvement strategy. A descriptive qualitative method with a single case study design was used, involving all 28 CV employees. Asanka Wijaya as a census sample. Data were collected through questionnaires and analyzed using a qualitative descriptive approach supported by quantitative data through SWOT Analysis, including IFAS and EFAS matrices. The results of the analysis show that the company's internal conditions are in the strong category (IFAS score 3.20), and the external environment offers greater opportunities than threats (EFAS score 3.20). The SWOT quadrant position position places CV. Asanka Wijaya in Quadrant I, indicates dominant internal strength and great external opportunities. Therefore, an aggressive strategy is recommended, focusing on optimizing employee performance, competence, and loyalty to expand the market and increase competitiveness, while also addressing existing internal weaknesses. This research is expected to provide strategic recommendations to optimize the potential of human resources in CV. Asanka Wijaya. Keywords: Strengths, Weakness, Opportunities, Threats, SWOT Analysis Abstrak Penelitian ini menganalisis kinerja karyawan di CV. Asanka Wijaya, sebuah perusahaan kosmetik, menggunakan analisis SWOT. Tujuannya adalah mengidentifikasi kekuatan, kelemahan, peluang, dan ancaman yang memengaruhi kinerja karyawan serta merumuskan strategi peningkatan kinerja yang tepat. Metode kualitatif deskriptif dengan desain studi kasus tunggal digunakan, melibatkan seluruh 28 karyawan CV. Asanka Wijaya sebagai sampel sensus. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan pendekatan deskriptif kualitatif yang didukung data kuantitatif melalui Analisis SWOT, termasuk matriks IFAS dan EFAS. Hasil analisis menunjukkan bahwa kondisi internal perusahaan berada pada kategori kuat (skor IFAS 3,20), dan lingkungan eksternal menawarkan peluang lebih besar daripada ancaman (skor EFAS 3,20). Penentuan posisi kuadran SWOT menempatkan CV. Asanka Wijaya pada Kuadran I, mengindikasikan kekuatan internal dominan dan peluang eksternal yang besar. Oleh karena itu, strategi agresif direkomendasikan, dengan fokus pada pengoptimalan kinerja, kompetensi, dan loyalitas karyawan untuk memperluas pasar serta meningkatkan daya saing, sambil juga mengatasi kelemahan internal yang ada. Penelitian ini diharapkan memberikan rekomendasi strategis untuk mengoptimalkan potensi sumber daya manusia di CV. Asanka Wijaya. Kata Kunci: Strengths, Weakness, Opportunities, Threats, SWOT Analysis